2022
DOI: 10.1101/2022.09.21.508904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro evidence against productive SARS-CoV-2 infection of human testicular cells: Bystander effects of infection mediate testicular injury

Abstract: The hallmark of severe COVID-19 involves systemic cytokine storm and multi-organ failure including testicular injury and germ cell depletion. The ACE2 receptor is also expressed in the resident testicular cells however, SARS-CoV-2 infection and mechanisms of testicular injury are not fully understood. The testicular injury can likely result either from direct virus infection of resident cells or by exposure to systemic inflammatory mediators or virus antigens. We here characterized SARS-CoV-2 infection in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…As expected, the virus was cleared from the lungs by D8 (Fig. S1C and D) and there was no infectious virus detected in the testis as shown in our previous study (21) and Fig. S1D.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…As expected, the virus was cleared from the lungs by D8 (Fig. S1C and D) and there was no infectious virus detected in the testis as shown in our previous study (21) and Fig. S1D.…”
Section: Resultssupporting
confidence: 86%
“…However, a recent longitudinal cohort study indicated a significant increase in inflammatory and linked to multiple-organ damage and immune dysfunction during both acute stage of disease and in long COVID patients (23,24). Our data obtained with the K18-hACE2 transgenic mice demonstrated gross pathology in the testis during the acute stage of the disease (21) similar to testicular injury observed in post-mortem COVID patients, thus supporting the use of these mice to assess the long-term impact of SARS-CoV-2 infection on testes.…”
Section: Introductionmentioning
confidence: 44%
See 2 more Smart Citations
“…However, exposure of seminiferous tubule cells and human testicular organoids to inflammatory supernatant from infected airway epithelial cells and Covid‐19 plasma decreased cell viability and resulted in the death of undifferentiated spermatogonia. Authors of this study also suggest that exposure of testicular cells to both cytokine storm and viral antigens may trigger pathological pathways and apoptotic death of germ cells that may be responsible for orchitis symptoms and lower sperm counts reported in Covid‐19 patients 69 …”
Section: Comorbidities Associated With Covid‐19 Morbidity and Mortali...mentioning
confidence: 67%